KEPUTUSAN PEMBELIAN DI PENGARUHI OLEH PROMOSI PENJUALAN PADA KLINIK KECANTIKAN DI GARUT - hari mulia (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The phenomenon of the emergence of skin beauty treatments in Garut is growing rapidly along with consumer awareness to take care of their skin. However, in the last 3 years there has been a decline in customers for beauty treatments. In this regard, a research was conducted at a beauty clinic in Garut with the title